Design of an experimental platform to investigate the effects of audible sounds on plant growth - Weiming, Cai; Songming, Zhu; Wang, Ning; Huinong, He; Beihua, Ying (International Journal of Agricultural and Biological Engineering, 2015)
An experimental platform was developed to investigate the effects of audible sound (20 Hz to 20 MHz) on plant growth promotion, which included a microcontroller-based embedded system for audible sound adjustment and analysis. The direct digital frequency synthesis (DDFS) method was used to generate various waveforms of sound in the platform. Soundproof glass and mufflers were used to reduce background noise. The developed system was tested on various plants, including hydroponic tomatoes, celery and mung bean. The testing results showed that the developed platform could produce pure tone and mixing audible sound with high stability and accuracy, make octave analysis of the sound under experimental environments, and the background noise in the testing chamber of the platform was lower than 55 dB(A) when the compression engine was working. The developed experimental platform has a great potential on facilitating scientific research on acoustic biology effects on plants and collecting real-time experimental data. Keywords: plant growth, background noise, acoustic biology effect, direct digital frequency synthesis, sound sensor DOI: 10.3965/j.ijabe.20150805.1556 Citation: Cai W M, Zhu S M, Wang N, He H N, Ying B H. Design of an experimental platform to investigate the effects of audible sounds on plant growth. Int J Agric & Biol Eng, 2015; 8(5): 162－169.